Basal-like progenitor cells: A review of dysplastic alveolar regeneration and remodeling in lung repair (2020)
Despite the central importance of the respiratory system, the exact mechanisms governing lung repair after severe injury remain unclear. The notion that alveolar type 2 cells (AT2s) self-renew and differentiate into alveolar type 1 cells (AT1s) does not fully encompass scenarios where these progenitors are severely affected by disease, e.g., H1N1 influenza or SARS-CoV-2 (COVID-19). Intrapulmonary p63+ progenitor cells, a rare cell type in mice but potentially encompassing more numerous classic basal cells in humans, are activated in such severe injury settings, proliferating and migrating into the injured alveolar parenchyma, providing a short-term ‘‘emergency’’ benefit. While the fate of these cells is controversial, most studies indicate that they represent a maladaptive repair pathway with a fate restriction toward airway cell types, rarely differentiating into AT2 or AT1 cells. Here, we discuss the role of intrapulmonary basal-like p63+ cells in alveolar regeneration and suggest a unified model to guide future studies.